Developing selective histone deacetylases (HDACs) inhibitors through ebselen and analogs - Wang Y; Wallach J; Duane S; Wang Y; Wu J; Wang J; Adejare A; Ma H (Dove Medical Press, 2017)
Yuren Wang,1 Jason Wallach,2 Stephanie Duane,1 Yuan Wang,1 Jianghong Wu,1 Jeffrey Wang,1 Adeboye Adejare,2 Haiching Ma1 1Reaction Biology Corp., Malvern, 2Department of Pharmaceutical Sciences, Philadelphia College of Pharmacy, University of the Sciences, Philadelphia, PA, USA Abstract: Histone deacetylases (HDACs) are key regulators of gene expression in cells and have been investigated as important therapeutic targets for cancer and other diseases. Different subtypes of HDACs appear to play disparate roles in the cells and are associated with specific diseases. Therefore, substantial effort has been made to develop subtype-selective HDAC inhibitors. In an effort to discover existing scaffolds with HDAC inhibitory activity, we screened a drug library approved by the US Food and Drug Administration and a National Institutes of Health Clinical Collection compound library in HDAC enzymatic assays. Ebselen, a clinical safe compound, was identified as a weak inhibitor of several HDACs, including HDAC1, HDAC3, HDAC4, HDAC5, HDAC6, HDAC7, HDAC8, and HDAC9 with half maximal inhibitory concentrations approximately single digit of µM. Two ebselen analogs, ebselen oxide and ebsulfur (a diselenide analog of ebselen), also inhibited these HDACs, however with improved potencies on HDAC8. Benzisothiazol, the core structure of ebsulfur, specifically inhibited HDAC6 at a single digit of µM but had no inhibition on other HDACs. Further efforts on structure–activity relationship based on the core structure of ebsulfur led to the discovery of a novel class of potent and selective HDAC6 inhibitors with RBC-2008 as the lead compound with single-digit nM potency. This class of histone deacetylase inhibitor features a novel pharmacophore with an ebsulfur scaffold selectively targeting HDAC6. Consistent with its inhibition on HDAC6, RBC-2008 significantly increased the acetylation levels of α-tubulin in PC-3 cells. Furthermore, treatment with these compounds led to cell death of multiple tumor cell lines in a dose-dependent manner. These results demonstrated that ebselen and ebsulfur analogs are inhibitors of HDACs, supporting further preclinical development of this class of compounds for potential therapeutic applications. Keywords: HDAC, inhibitor, ebselen, RBC-2008, screening, compound library, drug discovery